Določitev lokalnega geomagnetnega indeksa K ( = Determination of local geomagnetic K-index) - Rudi Čop; Damir Deželjin; Robert De Reggi (Geodetski Vestnik, 2015)
In this article, we present the origin of geomagnetic K-index. The International Association for Geomagnetism and Aeronomy (IAGA) recommends it for daily descriptions of geomagnetic field activity. The index is based on continuous measurements in a geomagnetic observatory on the Earth’s surface. We carried out measurements in Slovene Istria, which enabled us to calculate the local geomagnetic index for Slovenia. In Discussion and Conclusions, we also present some drawbacks of the index and plans for our future activities in this field.